Security Urbanism and the Counterterror State in Kenya. (September 2017) - Glück, Zoltán
This article offers a theoretical and ethnographic analysis of what I am calling 'security urbanism', examining the spatial practices of the Kenyan security state and the urban impacts of the War on Terror in Nairobi. From counterterror policing to forced disappearances, demolitions, military operations and the proliferation of checkpoints and security searches, the War on Terror has left its indelible material and affective impacts in Kenya. Counterterrorist policing operations such Operation Usalama Watch have left many marginalized Nairobi residents fearful and traumatized. Meanwhile, in rich suburbs, the twin specters of terrorism and crime fuse in the imaginations and gated compounds of the affluent. This article analyzes the urban, state and spatial transformations produced by the War on Terror across several geographical scales (from the highly local to the neighborhood and the national). In a first section, I focus on the 'state spatial strategies' of counterterrorism and analyze the emergence of a 'counterterror state' in Kenya. In a second section, I draw on several ethnographic vignettes to demonstrate how urban residents internalize and perform fears, fantasies and politics thoroughly saturated by the imaginaries of the War on Terror. Ultimately, I argue that Nairobi's security urbanism is the material articulation of War on Terror at the scale of the city, produced through the confluence of state strategies and everyday practices of securitized urban subjects. But how stable is the new hegemony of security in the country?